2006
DOI: 10.1021/bi061415l
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Fatty Acid Spin Labels within a Binding Site of Soybean Lipoxygenase-1

Abstract: The putative substrate-binding site in lipoxygenases is long and internal. There is little direct evidence about how the unsaturated fatty acid substrates enter and move within the cavity in order to position correctly for electron transfer reactions with the catalytic non-heme iron. An EPR spectroscopy approach, with spin labeled fatty acids, is taken here to investigate dynamic behavior of fatty acids bound to soybean lipoxygenase-1. The probes are labeled on carbons 5-, 8-, 10-, 12-and 16-of stearic acid. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
(94 reference statements)
1
17
1
1
Order By: Relevance
“…It has been shown that correlation times vary with the positions in DOXYL-labeled stearic acid (6.5 ns for 5-SDA, 12.4 ns for 10-SDA) [61]. We used an estimated correlation time τ c in calculating the distance from the PRE data of 1 ns.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that correlation times vary with the positions in DOXYL-labeled stearic acid (6.5 ns for 5-SDA, 12.4 ns for 10-SDA) [61]. We used an estimated correlation time τ c in calculating the distance from the PRE data of 1 ns.…”
Section: Discussionmentioning
confidence: 99%
“…For instance,t he spin labeled stearic acid derivative 8-DSA,w ith nine methylenes on the terminal methyle nd, has 31 mm affinity in solution. [50]…”
Section: Spin Label Studies Of Lipoxygenasementioning
confidence: 99%
“…Полиненасыщенная жирная кислота (субстрат) попадает в активный центр энзима через полость, обогащеннyю остатками гидрофобных аминокислот (около 50). Вход в эту полость на поверхности соевой ЛОГ1 находится между Trh 259 и Leu 541 и направлен в сторону С-терминального изолейцина и лигандов железа (гистидинов) [30,35]. Эта объемная полость формирует два изгиба: один возле атома железа, другой -в конце полости.…”
Section: особенности структурной организации липоксигеназunclassified